Memberdayakan Remaja Melalui Pendidikan Kesehatan Berpusat pada Individu: Efektivitas Metode Brainstorming Menggunakan Media E-Booklet terhadap Pengetahuan dan Sikap Remaja Tentang Bullying - Mona Megasari; Emi Salmiyah; Syifa Sri Rahayu (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2025)
Adolescent bullying is a major public health issue harming mental health, emotions, and academics. Person-centered, community-based education is key for awareness and prevention among students. This study aimed to evaluate the effectiveness of a person-centered health education method using brainstorming sessions supported by e-booklet media to improve adolescents’ knowledge and attitudes toward bullying. A quasi-experimental design was conducted at a junior high school in West Java, Indonesia, involving 54 students divided into intervention and control groups. The intervention group received health education through brainstorming sessions supported by an interactive e-booklet, while the control group received a conventional lecture. Data were analyzed using appropriate non-parametric statistical tests. The intervention group showed a statistically significant improvement in both knowledge and attitudes compared to the control group (p < 0.05). The brainstorming method encouraged active participation and emotional engagement, while the e-booklet served as an accessible and engaging educational tool for adolescents. This study highlights the importance of community-based, person-centered approaches in adolescent health promotion. Engaging students through interactive and reflective methods enhances knowledge and fosters positive attitudes. The integration of digital media in health education can be an effective strategy to increase awareness and prevent bullying in school setting